Performance analysis for single-stage and multi-stage coreless axial flux permanent magnet generator with different rotor structures / Asiful Habib - Asiful , Habib (2020)
Axial flux permanent magnet (AFPM) generator is a good candidate for both low and high-speed applications. Compared to radial flux machines, AFPM generators can be easily cascaded for enhanced power/torque while maintaining a fixed machine diameter. To improve power density and reduce cogging torque, some researchers have proposed the removal of iron core in the stator of AFPM machine, giving rise to the concept of coreless AFPM machine. Nevertheless, most of these coreless machines still require back iron on the rotor and/stator to reduce leakage flux. In this project, different rotor structures for single-stage coreless AFPM generators were considered, using two types of magnet arrays: i.e. conventional and Halbach magnet arrays, and two types of rotor materials, i.e. epoxy and iron rotors. The performances of the generators with different rotor structures were evaluated using ANSYS Maxwell® finite element analysis (FEA) software. The results showed that AFPM generator using iron rotor with conventional magnet array gave the overall best performance, even though epoxy rotor with Halbach array demonstrated comparable performance in terms of power density. Based on the findings from the single-stage coreless AFPM generators, the performance of multistage coreless AFPM generators were studied. It was found that by using epoxy rotors with a combination of conventional and Halbach magnet array, a hybrid multi-stage coreless AFPM generator with improved performance can be obtained. Compared to directly cascading multiple single-stage AFPM generators, the multi-stage AFPM generator with hybrid rotor gave better torque density as well as lower torque ripples.